Design and Synthesis of Novel Small Molecule Antimicrobials - Brown, Carla (My University, 2017)
Antimicrobial resistance is a significant threat to global health, and it is necessary to identify new drugs and drug targets for pathogenic bacteria, parasites, viruses, and fungi. Novel small molecules with antimicrobial activity may be discovered in the lab through chemical synthesis or from nature as secondary metabolites. This thesis describes our efforts to synthesize and identify antiparasitic and antiviral small molecules. The preparation of 3-diarylether quinolines with 5 μM activity against the parasite T. gondii, through a novel TFA-catalysed Povarov reaction using enol ethers as carbonyl surrogates is described. Libraries of quinazolinone and dihydroquinazolinone derivatives have been prepared through a multicomponent synthetic route. Structure activity relationship analysis allowed for differentiation of the antiparasitic pharmacophore from the antiviral pharmacophore, as well as the identification of compounds with single digit micromolar activity against both T. gondii and Herpes Simplex Virus 1. This work also details the design and synthesis of B-ring aza-analogs of bioactive Amaryllidaceae alkaloids in just 5 steps from chiral pool reagents. Aza-substitution of the B-ring eliminated antiviral activity, and this modification may also affect anticancer activity. Analysis of several natural product sources has also identified novel small molecules. Isolation of metabolites from Xylaria polymorpha identified three novel polyketide derivatives with unknown biological activity. The alkaloid candicine was found to be the primary polar metabolite from Ficus benjamina latex, as well as a potent inhibitor of murine cytomegalovirus. By identifying the mechanisms of action of these bioactive small molecules, we may identify targets for further drug development.
Keywords: organic chemistry; chemical biology